Narrative medicine — outline of issues - Zurzycka, Patrycja; Radzik, Teresa (Nursing Problems / Problemy Pielęgniarstwa, 2015)
Narrative medicine, by focusing on the patient’s individuality, is a response to an objective treatment of the patient boiling them down to a sum of bio-medical phenomena, skipping over psycho-social and cultural aspect of their functioning. Practicing of narrative includes listening to the patients’ stories including the biographical, psychological and socio-cultural context of their disease, coping with the disease as well as narratives conducted by professionals basing upon their professional experience in dealing with patients. Narrative medicine does not replace traditional medicine based upon evidence, but complements it, because openness to humanistic aspects of the disease helps get a lot of information is relevant in the therapeutic process, which might be omitted in the case of perceiving the patient only in terms of bio-medical disorders. The aim of the study was to discuss some issues related to the practice of narrative medicine in nursing.